2020
DOI: 10.1002/pchj.411
|View full text |Cite
|
Sign up to set email alerts
|

State anxiety and cardiovascular activity in an academic examination

Abstract: Exam is an academic stressor that frequently triggers the affective reaction of anxiety, as well as psychophysiological changes in the autonomic nervous system. Anxiety is a negative affective variable associated with a low level of performance. This study examined the impact of an academic exam on state anxiety (SA) levels and the effects on cardiovascular activity during its performance, as well as its possible influence on the score. The study group was composed of 122 female university students. Cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…5), possibly due to the performance's negative appraisal, whether live or prerecorded. This finding is not new, as several reports have documented the negative relationship between state anxiety and academic test performance (e.g., Gómez-Íñiguez et al 2021;Seipp 1991). The here-found connection could be due to higher state anxiety, possibly due to negative performance appraisal toward the end of the test, by either group, which was later indeed mirrored in lower grades.…”
Section: Do State and Trait Measures Mediate The Relationship Between...supporting
confidence: 60%
“…5), possibly due to the performance's negative appraisal, whether live or prerecorded. This finding is not new, as several reports have documented the negative relationship between state anxiety and academic test performance (e.g., Gómez-Íñiguez et al 2021;Seipp 1991). The here-found connection could be due to higher state anxiety, possibly due to negative performance appraisal toward the end of the test, by either group, which was later indeed mirrored in lower grades.…”
Section: Do State and Trait Measures Mediate The Relationship Between...supporting
confidence: 60%
“…erefore, vital signs such as BP, HR, RR, and SpO 2 are essential for monitoring adverse events [1,31]. Furthermore, chronic stress and high anxiety levels are associated with altered physiological states, especially in the autonomic nervous system, which can lead to high HR, hypertension, and CVD [32,33]. Several RCTs have reported that foot reflexology affects cardiovascular-related parameters and reduces patient fatigue, but the results are inconsistent [8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Khususnya, dalam konteks penilaian prestasi akademik, pelajarpelajar mengalami tahap tinggi kebimbangan yang selalunya mempunyai pengaruh negatif terhadap prestasi mereka. Kebimbangan boleh difahami sebagai pembolehubah afektif negatif yang dikaitkan dengan tahap prestasi yang rendah (Gómez-Íñiguez, Rodríguez, & Cantero, 2021). Kajian ini mempunyai objektif yang jelas sekali di mana kajian ini ingin meneliti kesan kebimbangan terhadap prestasi akademik melalui pendekatan ulasan naratif terhadap kajian-kajian lepas.…”
Section: Pendahuluanunclassified